Participatory mapping and spatial planning for renewable energy development: The case of ground-mount solar in rural Ontario - Kirby Calvert; Rebecca Jahns (Canadian Planning and Policy, 2021)
Displacing fossil fuels with renewable energy resources is essential to mitigate climate change. The implementation of renewable energy systems brings stark changes to local landscapes; e.g., wind turbines dotting a rural landscape, or solar panels covering fertile land that previously supplied food. These changes can evoke strong social opposition, even among people who are generally supportive of renewable energy (RE). Research suggests that public tensions around renewable energy development are reduced through inclusive decision-making processes (i.e., improved procedural justice) as well as benefits sharing (i.e., improved distributional justice). We develop and test a process for proactive and inclusive spatial planning for RE development in a region. Our work combines participatory mapping and survey- and focus-group-based sentiment analysis in order to understand community concerns around renewable energy projects, and how those concerns are reflected spatially. We conducted a case study on ground-mount solar energy systems in the Town of Caledon, Ontario, Canada. From this study, we aimed to determine what regions and kinds of landscapes community members might find acceptable or not for new solar projects, and to facilitate dialogue about opportunities and potential impacts with the general public, key stakeholders, and influencers (utilities, land-owners, developers, municipal staff) in the locality.